Deformação plástica severa da liga Ti-13Nb-13Zr - Godoy Pérez, Diego Alfonso (2017)
Biomedical devices currently in use (prostheses, implants) have satisfactory performance in many cases. However, sometimes the body reacts to the device insertion and may lead to its rapid replacement. Some of these disadvantages can be solved by the use of titanium and its alloys, due to their excellent combination of corrosion resistance, wear resistance and biocompatibility compared to other competing biomaterials. This work presents the possibility of obtaining near β titanium alloy with ultrafine grains produced by severe plastic deformation. For this, the Ti-13Nb-13Zr alloy was processed by high-pressure torsion processing method. Samples were processed with different loads and number of turns. The samples were evaluated by Vickers microhardness. As-received and deformed samples were analyzed through X-Ray diffraction. The microstructures were observed by optical microscopy and scanning electron microscope and the microtexture and phase mappings of the material evaluated through the ASTAR equipment in the transmission electron microscope. After characterization, it was observed that there is a refinement of the microstructure and increase of the microhardness of the Ti-13Nb-13Zr alloy deformed by HPT. Due to the superior microhardness of the deformed material and the results of phase transformations indicate a potential application as nanostructured biomaterial.